Pengaruh Leverage, Profitabilitas dan Struktur Modal Terhadap Manajemen Laba: Pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di BEI Periode 2019-2023 - Herman Wijaya; Media Listiana Rahayu (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study examines the influence of leverage, profitability, and capital structure on earnings management in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Earnings management has become a central issue in financial reporting, as it reflects managerial discretion in presenting financial information that may not fully align with the company’s actual economic condition. Understanding the determinants of earnings management is therefore essential to enhance transparency, credibility, and stakeholder trust in corporate financial reports. The research employed a quantitative approach using multiple linear regression analysis, with data processed through SPSS version 25. The sample consisted of 104 company-year observations, which were selected using purposive sampling techniques and subsequently refined through outlier testing to ensure data validity and reliability. The independent variables analyzed were leverage, profitability, and capital structure, while earnings management served as the dependent variable. The empirical findings demonstrate that leverage and profitability exert a significant influence on earnings management practices. Specifically, companies with higher leverage tend to engage in earnings management as a mechanism to meet financial obligations and reduce the risk of violating debt covenants. Similarly, higher profitability motivates managers to manipulate earnings in order to sustain investor confidence and maintain a favorable corporate image. In contrast, capital structure is found to have no significant effect on earnings management, indicating that financing decisions between debt and equity may not directly influence managerial behavior in financial reporting. These results highlight the importance of monitoring leverage and profitability indicators as potential predictors of earnings management. For corporate management, the findings suggest the need to implement stronger internal control systems and uphold ethical financial practices. For investors and regulators, the study provides useful insights into assessing company performance beyond reported earnings, thereby supporting more informed decision-making and promoting the integrity of capital markets.